The Forkhead Transcription Factor Foxl2 Is Sumoylated in Both Human and Mouse: Sumoylation Affects Its Stability, Localization, and Activity - Marongiu, Mara; Deiana, Manila; Meloni, Alessandra; Marcia, Loredana; Puddu, Alessandro; Cao, Antonio; Schlessinger, David; Crisponi, Laura (PloS one, 2010)
The FOXL2 forkhead transcription factor is expressed in ovarian granulosa cells, and mutated FOXL2 causes the blepharophimosis, ptosis and epicanthus inversus syndrome (BPES) and predisposes to premature ovarian failure. Inactivation of Foxl2 in mice demonstrated its indispensability for female gonadal sex determination and ovary development and revealed its antagonism of Sox9, the effector of male testis development. To help to define the regulatory activities of FOXL2, we looked for interacting proteins. Based on yeast two-hybrid screening, we found that FOXL2 interacts with PIAS1 and UBC9, both parts of the sumoylation machinery. We showed that human FOXL2 is sumoylated in transfected cell lines, and that endogenous mouse Foxl2 is comparably sumoylated. This modification changes its cellular localization, stability and transcriptional activity. It is intriguing that similar sumoylation and regulatory consequences have also been reported for SOX9, the male counterpart of FOXL2 in somatic gonadal tissues.